Job satisfaction and caring behavior among nurses in a military hospital: A cross-sectional study - Kuswantoro Rusca Putra; Tutut Andayani; Evi Harwiati Ningrum (SAGE Publishing, 2021)
Background: Caring is the major focus of nursing practice, and their behavior has an impact on the quality of patient care, and it is very important that they are satisfied while working. The strong relationship between job satisfaction and nurses caring behavior is well established, and therefore the managers can be encouraged to provide better conditions for nurses' satisfaction. The aim of this study was to investigate the relationship between job satisfaction and the caring behavior of nurses in the Military Hospital. Design and Methods: A survey with a self-assessment questionnaire was carried out from August to December 2019.  Participants were 121 nurses working in a military hospital Malang, Indonesia. The data was collected using the Job Satisfaction Survey (JSS) and Caring Behavior Inventory (CBI-24). The data were analyzed using rank Spearman and multiple linear regression. Results: Job satisfaction had a positive correlation with the caring behavior of nurses (p=0.003; r=0.266). Furthermore, there were four job satisfaction dimensions namely supervision, contingent rewards, co-workers, nature of work and communication dimensions were positively correlated with nurses' caring behavior (p<0.05) while the Whilst pay, promotion, benefits, operating procedure dimensions are not related to nurse's caring behavior (p>0.05). Conclusions: Caring behavior of nurses is influenced by job satisfaction. Therefore, it is necessary to provide supervision, contingent rewards, empowerment, collaboration program for the nurses to reconstruct the nursing working environment to be healthier and increase the caring behavior of nurses.